2021
DOI: 10.1177/00027162211028822
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Recoveries: Wealth, Race, and the Working Class after the Great Recession

Abstract: What does it mean to be working class in a society of extreme racial wealth inequality? Using data from the Survey of Consumer Finances, we investigate the wealth holdings of Black, Latinx, and white working-class households during the post–Great Recession (pre–COVID-19) period that spanned 2010 to 2019. We then explore the relationship between working-class and middle-class attainment using a wealth-based metric. We find that, in terms of their net worth, fewer Black working-class households benefitted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…121–137). Additionally, research has found that Black households benefitted less from the post-Great Recession economic recovery compared to white working class households, and that Black households saw a much greater fraction of their wealth eliminated due to the Recession than did white households ( Addo & Darity, 2021 ). Since housing insecurity is worse for the health of Black adults, policies that improved housing security would disproportionately benefit Black adults and could reduce disparities in health.…”
Section: Discussionmentioning
confidence: 99%
“…121–137). Additionally, research has found that Black households benefitted less from the post-Great Recession economic recovery compared to white working class households, and that Black households saw a much greater fraction of their wealth eliminated due to the Recession than did white households ( Addo & Darity, 2021 ). Since housing insecurity is worse for the health of Black adults, policies that improved housing security would disproportionately benefit Black adults and could reduce disparities in health.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that upward or downward income trajectories may result in different patterns from the ones we identified here. Key historical events, such as the Great Recession, might play an important role, so future researchers might explore how they impact the association explored here because Black and White men were differentially impacted by them ( Addo & Darity, 2021 ; Thomas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are ever more sources of accumulation for white families, my results for black families indicate effects of economic insecurity. Fewer routes are available for blacks to carry their wealth across multiple generations, which is a reminder of the missing black bourgeoisie (Addo & Darity, 2021; Darity et al., 2021), and the peculiar imbalance of portfolio asset types. An underlying context for that portfolio imbalance is that when slavery ends, black people in the South manage to move from abject poverty to wealth (Washington & DuBois, 1907).…”
Section: Discussionmentioning
confidence: 99%
“…Although wealth is an important source of economic security (Addo & Darity, 2021; Altonji & Doraszelski, 2005; Blau & Graham, 1990; Darity et al., 2021; Gale & Scholz, 1994; King & Dicks‐Mireaux, 1982; Oliver & Shapiro, 2006; Taylor & Meschede, 2018; Thomas et al., 2018; Shapiro, 2004), the literature on the intergenerational transmission of wealth is far more limited. A few scholars focus on the association between the wealth portfolio composition of parents and the portfolio of their children (Chiteji & Hamilton, 2005; Chiteji & Stafford, 1999).…”
Section: Introductionmentioning
confidence: 99%